Treatment of Masked Hypertension with a Chinese Herbal Formula: A Randomized, Placebo-Controlled Trial. Issue 19 (10th November 2020) - Zhang, Dong-Yan; Cheng, Yi-Bang; Guo, Qian-Hui; Shan, Xiao-Li; Wei, Fang-Fei; Lu, Feng; Sheng, Chang-Sheng; Huang, Qi-Fang; Yang, Chuan-Hua; Li, Yan; Wang, Ji-Guang
Abstract : Background: Masked hypertension is associated with adverse cardiovascular outcomes. Nonetheless, no randomized controlled trials exist in the treatment of masked hypertension. The aim of this randomized, placebo-controlled trial was to investigate the efficacy and safety of blood pressure (BP)–lowering treatment with a Chinese herbal formula, gastrodia-uncaria granules, in patients with masked hypertension. Methods: Patients with an office BP of <140/90 mm Hg and daytime ambulatory BP of 135 to 150 mm Hg systolic or 85 to 95 mm Hg diastolic were randomly assigned 1:1 to the treatment of gastrodia-uncaria granules or placebo 5 to 10 g twice daily for 4 weeks. The primary efficacy variable was the change in daytime ambulatory BP. Results: At baseline, office and daytime BP of the 251 participants (mean age, 50.4 years; 53.4% men; mean body mass index 24.5 kg/m 2 ; and 2.8%, 1.6%, and 30.7% with cardiovascular disease, diabetes, and smoking, respectively) averaged 129/82 and 135/89 mm Hg, respectively. In the intention-to-treat analysis, daytime systolic/diastolic BP was reduced by 5.44/3.39 and 2.91/1.60 mm Hg in the gastrodia-uncaria granules and placebo groups, respectively. The between-group difference in BP reductions was significant for the daytime (2.52/1.79 mm Hg; P ⩽0.025) and 24-hour BP (2.33/1.49 mm Hg; P ⩽0.012), but not for the clinic and nighttime BPs ( P ≥0.162). The per-protocol analysis in 229 patients produced similar results. Only 1 adverse event (sleepiness during the day) was reported, and no serious adverse event occurred. Conclusions: BP-lowering treatment with Chinese traditional medicine gastrodia-uncaria granules is efficacious for patients with masked hypertension. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02156024. Abstract : Supplemental Digital Content is available in the text.